Effect of Pregelatinization on Suweg Tuber Starch (Amorphophallus Paeonifolius) as Tablet Crusher - Dwi Setyawan (Journal of Global Pharma Technology, 2020)
Background: Disintegrant tablet from starch is more often used to crush the tablet that has been swallowed. However, the material of this starch is tablet crusher which very weak. In contrast to the suweg starch (Amorphophallus paeonifolius) which has undergone pregelatinization where the content of amylose and amylopectin and the water absorption capacity that is high enough so that it can crush the tablet quickly. The aim of this study was to determine the influence of pregelatinization towards elephant foot yam (Amorpophallus paeonifolius) starch as disintegrant against tablet physical quality profile of the Paracetamol tablet. Method: The research was carried out by making suweg natural starch which then it made a suspension in the water with a concentration of 20% and heated to the temperature of 60 ± 5 0C and 70 ± 5 0C within 15 minutes. After the suweg pregelatin starch has been made, then a paracetamol tablet and a qualitative examination also made which includes the determination of the paracetamol infrared spectrum, the examination of moisture content, the testing with iodine, the testing with optical microscopy, X-ray diffraction analysis, the starch thermal analysis with DTA, and the examination of swelling power which then compared to each tablet formula made by the wet granulation method. after that, it was continued with the examination of the granule quality, including the examination of moisture content, the examination of granule particle size and number of fines, the examination of flow velocity and rest angle of the granule. Moreover, it was carried out an evaluation of the paracetamol tablet physical quality in the form of hardness test, friability test, and disintegration time test. The data obtained was further analyzed by One Way ANOVA. Result: Tablet formula with pregelatinization of suweg natural starch can reduce the hardness, increased the tablet disintegration time, and made no difference in friability compared to the formulas containing natural suweg tuber starch and SSG. The result of increased disintegration time was then compared with the result of the swelling power test, but did not indicate a correlation both of them. The different of disintegration was not showed a correlation with values of swelling power. Keywords: Suweg Tuber Starch, Starch Pregelatinization, Pregelatinized Starch Tablet.